The low affinity neurotrophin receptor CD271 regulates phenotype switching in melanoma. Issue 1 (December 2017) - Restivo, Gaetana; Diener, Johanna; Cheng, Phil; Kiowski, Gregor; Bonalli, Mario; Biedermann, Thomas; Reichmann, Ernst; Levesque, Mitchell; Dummer, Reinhard; Sommer, Lukas
Abstract Cutaneous melanoma represents the most fatal skin cancer due to its high metastatic capacity. According to the "phenotype switching" model, the aggressive nature of melanoma cells results from their intrinsic potential to dynamically switch from a high-proliferative/low-invasive to a low-proliferative/high-invasive state. Here we identify the low affinity neurotrophin receptor CD271 as a key effector of phenotype switching in melanoma. CD271 plays a dual role in this process by decreasing proliferation, while simultaneously promoting invasiveness. Dynamic modification of CD271 expression allows tumor cells to grow at low levels of CD271, to reduce growth and invade when CD271 expression is high, and to re-expand at a distant site upon decrease of CD271 expression. Mechanistically, the cleaved intracellular domain of CD271 controls proliferation, while the interaction of CD271 with the neurotrophin receptor Trk-A modulates cell adhesiveness through dynamic regulation of a set of cholesterol synthesis genes relevant for patient survival. The aggressive nature of melanoma cells relies on their ability to switch from a high-proliferative/low-invasive to a low-proliferative/high-invasive state; however, the mechanisms governing this switch are unclear. Here, using in vivo models of human melanoma, the authors show that CD271 is a key regulator of phenotype switching and metastasis formation.